Metalliferous mine closure geochemical risk planning and validation template - McCann, P; Pearce, S; Brookshaw, D (Mine Closure 2023: Proceedings of the 16th International Conference on Mine Closure, 2023)
Keywords: closure planning template; closure risks; closure geochemical risk; closure geochemical planning; mine closure governance